THE EXISTENCE OF ILMU SEJATI PEOPLE IN RELIGIOUS MODERATION : EKSISTENSI PENGHAYAT KEPERCAYAAN ILMU SEJATI DALAM MODERASI BERAGAMA - Jauhar, Moh. Irmawan; Ismatulloh, Muh. Kholid (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2022)
Believers have a long history-based existence where strengthened by religions that came to the archipelago.Perguruan Ilmu Sejati as one of the streams of believers is one of the varieties of wealth that has its owncharacteristics. Perguruan Ilmu Sejati has the teachings of harmony in society as an indicator of religiousmoderation. This article seeks to explore and provide interpretations for the typology of believers inPerguruan Ilmu Sejati in religious moderation and models of believers in Perguruan Ilmu Sejati in religiousmoderation. This research has a qualitative approach and the type is a case study. Data obtained by meansof interviews, observation, and documentation. Data analysis was carried out since data collection withthree steps namely data condensation, data display, and conclusion drawing/verification. The results of thestudy stated that there are three types of believers in the Perguruan Ilmu Sejati namely core members,strictmembers, and ordinary members. Each has a different character and also a way to apply an attitude ofreligious moderation. Two models of practicing Perguruan Ilmu Sejati in religious moderation are theflexibility and active role of members of the Perguruan Ilmu Sejati in society. Flexibility is built fromcommunication Intense internal work from members of the Perguruan Ilmu Sejati at the research location.The active role of Perguruan Ilmu Sejati members in social life starts with the example of the chairman forthe members. They feels called and wants to contribute positively for the common good in society